2019
DOI: 10.1021/acs.orglett.9b02899
|View full text |Cite
|
Sign up to set email alerts
|

i-Pr2NMgCl·LiCl Enables the Synthesis of Ketones by Direct Addition of Grignard Reagents to Carboxylate Anions

Abstract: The direct preparation of ketones from carboxylate anions is greatly limited by the required use of organolithium reagents or activated acyl sources that need to be independently prepared. Herein, a specific magnesium amide additive is used to activate and control the addition of more tolerant Grignard reagents to carboxylate anions. This strategy enables the modular synthesis of ketones from CO2 and the preparation of isotopically-labelled pharmaceutical building blocks in a single operation. Ketones (1) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Moreover,i tw as recently found that the same Grignard-DIPAMgCl•LiCl combinationi su niquely more reactive and more selectivei na ddition reactions to chal-lenging carboxylate anions. [18] This further suggests that an ew speciesi sf ormed in solution upon mixing Grignardr eagents 1 and DIPAMgCl•LiCl (4a), and this is relevant for the new reactivity observed.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover,i tw as recently found that the same Grignard-DIPAMgCl•LiCl combinationi su niquely more reactive and more selectivei na ddition reactions to chal-lenging carboxylate anions. [18] This further suggests that an ew speciesi sf ormed in solution upon mixing Grignardr eagents 1 and DIPAMgCl•LiCl (4a), and this is relevant for the new reactivity observed.…”
Section: Introductionmentioning
confidence: 90%
“…It was also found that LiCl (entry 4), and in particular the 1:1:1 stoichiometry between the Grignard, the base and LiCl, are critical for the success of this reaction (entries 5 and 6). Moreover, it was recently found that the same Grignard‐DIPAMgCl⋅LiCl combination is uniquely more reactive and more selective in addition reactions to challenging carboxylate anions [18] . This further suggests that a new species is formed in solution upon mixing Grignard reagents 1 and DIPAMgCl⋅LiCl ( 4 a ), and this is relevant for the new reactivity observed.…”
Section: Introductionmentioning
confidence: 92%
“…Unlike the prosperous development of carbon–heteroatom bond formation mentioned above, carbon–carbon bond‐forming reactions involving exhaustive carboxylic deoxygenation have remained elusive. On the contrary, the mono‐deoxygenative version, wherein the carboxylic acid behaves as an acyl equivalent, has seen prominent advancement in recent years [2, 4, 159–160] …”
Section: Deoxygenative Functionalizations Of Carboxylic Acidsmentioning
confidence: 99%
“…Decarboxylative radical addition reactions (Scheme A) have recently emerged as prime tools to create aliphatic ligations in biomolecules. , These methods take advantage of the abundance of carboxylic acids , and the various technologies developed with Michael acceptors. , Despite their success, radical addition reactions are slow (6–12 h) and require additional catalysts, inorganic reducing suspensions, and/or additives that are not native to biological systems . The abundance of endogenous carboxylic acids in biomolecules or biomatrices poses a selectivity challenge for carboxylic acid substrates ( 1 ), due to their similar oxidation potentials. In contrast, the N -hydroxyphthalimide (NHPI) esters ( 2 ) can be orthogonally activated in the presence of other carboxylates via single-electron reduction. ,,− Recent methods based on desymmetrization and late-stage carbene transfer illustrate the potential of redox-active esters to be introduced through strategies unavailable to the parent carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%